Lithium ion battery and electronic device

By forming convex and concave structures on the surface of the negative electrode sheet of the lithium-ion battery and adding DFEA and D2 to the electrolyte, the structural instability problem caused by volume expansion of the silicon-based negative electrode material is solved, and the high-temperature cycle stability of the battery is improved. Safety performance.

CN119208706AActive Publication Date: 2024-12-27ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411708071.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The volume expansion of the silicon-based anode material during charging and discharging of lithium-ion batteries leads to structural instability, reducing cycle stability and safety performance, especially in high-temperature environments, where there is a risk of thermal runaway.

Method used

Convex and concave structures are formed by embossing treatment on the surface of the negative electrode sheet, and ethyl 2,2-difluoroacetate (DFEA) and 1,1,2,2,-tetrafluoroethyl-2 are introduced into the electrolyte. ,2,3,3-tetrafluoropropyl ether (D2), regulates the ratio of its content and the sum of the positive projection area of ​​the convex part to the negative electrode sheet area, and optimizes the high-temperature cycling performance and safety of the battery.

Benefits of technology

It improves the high-temperature cycle stability and safety performance of the battery, reduces side reactions and electrolyte consumption, reduces the risk of thermal runaway, and enhances the chemical stability of the electrode-electrolyte interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208706A_ABST
    Figure CN119208706A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium ion battery and an electronic device comprising the lithium ion battery. The lithium ion battery comprises a negative plate and an electrolyte, the negative plate is provided with a first surface and a second surface which are back to back along the thickness direction, the first surface is provided with a plurality of convex parts, the second surface is provided with a plurality of concave parts, the convex parts correspond to the concave parts, and the ratio of the sum of orthographic projection areas of the convex parts on the first surface to the area of the negative plate is S; the negative plate comprises a negative current collector and a negative active material layer on at least one side surface of the negative current collector, and the negative active material layer comprises a silicon-based material; the electrolyte comprises 2, 2-ethyl difluoroacetate with the content of F1 and 1, 1, 2, 2,-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether with the content of F2, and (F1 + F2) / S is larger than or equal to 1.9 and smaller than or equal to 984. The lithium ion battery provided by the invention has the characteristics of long high-temperature cycle life and high safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium ion battery and an electronic device. Background Art

[0002] Silicon-based negative electrode materials are regarded as an important development direction for negative electrode materials of lithium-ion batteries due to their high specific capacity. However, silicon-based negative electrode materials have the problem of large volume expansion during charging and discharging, which leads to decreased structural stability of the electrode and incomplete shedding of active substances on the surface of the electrode, which reduces the cycle stability and safety performance of the battery, especially in high temperature environments. Summary of the invention

[0003] The object of the present invention is to overcome the above-mentioned problems existing in the prior art, and provide a lithium ion battery and an electronic device comprising the lithium ion battery, by adjusting the relationship between the content of ethyl 2,2-difluoroacetate and 1,1,2,2,-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in the electrolyte and the ratio of the sum of the orthographic projection areas of the protrusions on the first surface to the area of ​​the negative electrode sheet, the high temperature cycle performance and safety of the lithium ion battery of the present invention (hereinafter referred to as the battery) are optimized.

[0004] The inventors of the present invention have found that by embossing the surface of the silicon-based negative electrode sheet, a number of convex portions are formed on one side of the negative electrode sheet, and a number of concave portions are formed on the other side of the negative electrode sheet, so that the negative electrode active material can be pre-compressed, and its volume change during the charge and discharge process can be reduced, thereby reducing the crushing of the negative electrode active material and the damage to the electrode structure, which helps to improve the structural stability of the negative electrode sheet, avoid the negative electrode active material from falling off due to volume expansion during the charge and discharge process, ensure the integrity of the electrode structure, and improve the cycle stability of the battery. However, the inventors of the present invention have found that although the embossing treatment can alleviate the volume expansion of the silicon-based negative electrode, along with the advantages of increased contact area between the electrolyte and the negative electrode active material and increased reactive sites brought about by the embossing process, there is also the problem of more intense side reactions under high temperature conditions, which aggravates the consumption of the electrolyte and the generation of harmful gases, increases the internal pressure of the battery, deteriorates the high temperature performance, and increases the risk of thermal runaway.

[0005] In order to overcome the problem of poor high temperature performance and increased risk of thermal runaway caused by increasing the contact area between the electrolyte and the negative electrode sheet by embossing the silicon-based negative electrode, the inventor of the present invention has found through extensive research that introducing 2,2-difluoroethyl acetate (DFEA) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (D2) with good chemical stability and flame retardancy into the electrolyte helps to improve the stability of the electrolyte and the stability of the electrode-electrolyte interface, and by adjusting the relationship between the content of DFEA and D2 in the electrolyte and the ratio of the sum of the positive projection area of ​​the convex portion on the first surface to the area of ​​the negative electrode sheet, the electrolyte is adapted to the negative electrode sheet after embossing, thereby achieving the purpose of improving the high temperature performance of the battery, and improving the cycle life and safety.

[0006] Based on this, the inventors of the present invention propose the following solutions: In a first aspect, the present invention provides a lithium-ion battery, the lithium-ion battery comprising a negative electrode sheet and an electrolyte; the negative electrode sheet has a first surface and a second surface opposite to each other in a thickness direction, the first surface has a plurality of convex portions, the second surface has a plurality of concave portions, the convex portions correspond to the concave portions, and the ratio of the sum of the positive projection areas of the convex portions on the first surface to the area of ​​the negative electrode sheet is S, with a unit of 1; the negative electrode sheet comprises a negative electrode current collector and a surface located on at least one side of the negative electrode current collector A negative electrode active material layer is formed on the surface; the negative electrode active material layer comprises a silicon-based material; the electrolyte comprises ethyl 2,2-difluoroacetate and 1,1,2,2,-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, based on the total weight of the electrolyte, the content of ethyl 2,2-difluoroacetate is F1, and the content of 1,1,2,2,-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is F2; ​​F1, F2 and S satisfy 1.9≤(F1+F2) / S≤984.

[0007] A second aspect of the present invention provides an electronic device, which includes the lithium-ion battery according to the first aspect of the present invention.

[0008] Compared with the prior art, the present invention has at least the following effects: (1) In the present invention, by introducing DFEA and D2 into the electrolyte, their chemical stability and flame retardancy can be brought into play, the chemical stability of the electrolyte and the electrode-electrolyte interface can be improved, and a stable SEI film can be formed on the surface of the silicon-based material, thereby improving the high-temperature performance of the battery.

[0009] (2) In the present invention, by regulating the relationship between the content of DFEA and D2 in the electrolyte and the ratio of the sum of the orthographic projection areas of the protrusions on the first surface to the area of ​​the negative electrode sheet, the compatibility of the electrolyte and the embossed negative electrode sheet is improved, and the aggravation of the side reaction caused by the excessive contact area between the electrolyte and the negative electrode sheet is avoided, thereby further improving the cycle stability and safety of the battery under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 FIG. 1 is a schematic diagram showing the structure of the convex portion and the concave portion along the thickness direction of the negative electrode sheet in one embodiment of the present invention.

[0011] Figure 2 FIG. 1 is a schematic top view of a convex portion of a negative electrode sheet on a first surface in an embodiment of the present invention.

[0012] In the figure: 1. First surface; 2. Negative electrode current collector; 3. Second surface; 4. Protrusion. DETAILED DESCRIPTION

[0013] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0014] The first aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising a negative electrode sheet and an electrolyte; the negative electrode sheet has a first surface and a second surface opposite to each other in a thickness direction, the first surface has a plurality of convex portions, the second surface has a plurality of concave portions, the convex portions correspond to the concave portions, and the ratio of the sum of the positive projection areas of the plurality of convex portions on the first surface to the area of ​​the negative electrode sheet is S, with a unit of 1; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a silicon-based material; the electrolyte comprises ethyl 2,2-difluoroacetate and 1,1,2,2,-tetrafluoroethyl 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, based on the total weight of the electrolyte, the content of ethyl 2,2-difluoroacetate is F1, and the content of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is F2; ​​F1, F2 and S satisfy 1.9≤(F1+F2) / S≤984, for example, 1.9, 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 100, 150, 200, 300, 400, 500, 600, 700, 800, 900, 910, 920, 930, 940, 950, 960, 970, 975, 980, 982 or 984.

[0015] In one embodiment, 16.67≤(F1+F2) / S≤200.

[0016] In the present invention, the embossing treatment can be obtained by conventional techniques in the art, for example, by rolling an embossing roller on the surface of the negative electrode sheet; the sum of the orthogonal projection areas of the convex portion on the first surface has the conventional meaning in the art, and refers to the sum of the areas of the projection surfaces formed by the convex portion on the first surface when the parallel projection line is perpendicular to the first surface on the negative electrode sheet, and correspondingly, the orthogonal projection area formed by the concave portion is also present on the second surface. The correspondence between the convex portion and the concave portion means that the orthogonal projection of the convex portion on the first surface overlaps at least partially with the orthogonal projection of the concave portion on the second surface, and the former may fully cover the latter, or the latter may fully cover the former, or the two partially overlap. In some embodiments, the orthogonal projection area of ​​the convex portion on the first surface accounts for 80%-120% of the orthogonal projection area of ​​the concave portion on the second surface, for example, 80%, 90%, 100%, 110% or 120%.

[0017] like Figure 1 FIG. 1 is a schematic diagram of the structure of the convex and concave portions along the thickness direction of the negative electrode sheet in one embodiment of the present invention, wherein 1 is the first surface, 2 is the negative electrode current collector, and 3 is the second surface. It can be seen from the figure that the negative electrode current collector has a first surface and a second surface on both sides, the first surface has a convex portion, and the second surface has a concave portion; Figure 2 The figure shows a top view of the convex portion on the negative electrode sheet on the first surface in one embodiment of the present invention, wherein 1 is the first surface and 4 is the convex portion. It can be seen from the figure that there are several convex portions distributed on the first surface, and the orthographic projection of the convex portion on the first surface is a circle.

[0018] In the present invention, when the area of ​​the negative electrode sheet is determined, the larger the sum of the orthogonal projection areas of the protrusions on the first surface, the larger the contact area between the electrolyte and the negative electrode active material, which will not only accelerate the consumption of the electrolyte, but also the excessive sum of the orthogonal projection areas of the protrusions will lead to a decrease in the chemical stability of the electrolyte on the surface of the negative electrode sheet; when (F1+F2) / S<1.9, the ratio of the sum of the orthogonal projection areas of the protrusions on the first surface to the area of ​​the negative electrode sheet is too large, and the contents of DFEA and D2 are relatively low, and the improved stability of the electrolyte is not enough to improve the aggravated side reactions caused by the excessive contact area, thereby deteriorating the high-temperature cycle performance; when (F1+F2) / S>984, the ratio of the sum of the orthogonal projection areas of the protrusions on the first surface to the area of ​​the negative electrode sheet is too small, which is not conducive to inhibiting the volume expansion of the silicon-carbon material, the contents of DFEA and D2 are relatively high, and the viscosity of the electrolyte increases, thereby affecting the wettability of the electrolyte to the diaphragm and the electrode, and easily forming an unstable SEI film under high temperature conditions, resulting in a decrease in the high-temperature cycle life of the battery.

[0019] In the present invention, when calculating (F1+F2) / S, F1, F2 and S are only substituted into numerical calculations, and the units do not participate in the calculations. For example, when F1=6%, F2=3%, and S=0.24, (F1+F2) / S=(6+3) / 0.24=37.5.

[0020] In the present invention, S is 0.03-0.6, with the unit being 1, for example, 0.03, 0.04, 0.05, 0.075, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.45, 0.5, 0.52, 0.54, 0.56, 0.58 or 0.6.

[0021] In one embodiment, S is 0.1-0.4, with a unit of 1.

[0022] In the present invention, S can be measured by combining a scanning electron microscope with an image analysis software, for example: a scanning electron microscope is used to image the first surface of the negative electrode sheet having a plurality of protrusions, 10 different regions of the same area are selected at different magnifications on the obtained SEM image, and the ratio of the sum of the areas of the orthographic projections of the protrusions in each region to the area of ​​the region is measured and calculated, and finally the average value is taken to obtain S. The above test results can also be obtained by other conventional test methods in the art.

[0023] In the present invention, F1 is 1-20, and the unit is %, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0024] In one embodiment, F1 is 2-13, and the unit is %.

[0025] In the present invention, F2 is 0.1-10, and the unit is %, for example, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0026] In one embodiment, F2 is 2-7, and the unit is %.

[0027] In the present invention, embossing the surface of the silicon-based negative electrode sheet to form a convex portion can increase the specific surface area of ​​the silicon-based negative electrode active material, increase the contact area with the electrolyte, help the electrolyte to cover the surface of the negative electrode active material more evenly, and improve the wettability. However, at the same time, due to the increase in contact area and the increase in reactive sites, the side reactions under high temperature conditions are aggravated. Introducing DFEA and D2 with high chemical stability and non-flammability into the electrolyte can improve the oxidation stability and flame retardancy of the electrolyte, and form a stable SEI film on the surface of the silicon-based negative electrode sheet, which alleviates the occurrence of side reactions under high temperature conditions and improves the high temperature cycle life and safety of the battery. Among them, DFEA has high ionic conductivity and can make the SEI film on the surface of silicon-based materials have good thermal stability. D2, as a co-solvent of the electrolyte, not only prevents excessive oxidation of the electrolyte on the surface of the negative electrode, but also further improves the stability of the SEI film on the surface of the positive electrode, prevents oxidative decomposition of the electrolyte, but also alleviates the increase in viscosity caused by the addition of DFEA. DFEA will also make up for the low conductivity caused by the addition of D2. Therefore, the performance of DFEA and D2 is complementary. The stable solid electrolyte interphase (SEI) formed on the surface of the silicon-based negative electrode can mask the reaction active sites on the surface of the negative electrode, inhibit the decomposition of the electrolyte, reduce side reactions, and improve the high-temperature cycle stability and safety of the battery.

[0028] In the present invention, the negative electrode sheet is embossed to form a plurality of convex portions and a plurality of concave portions on both sides of the surface of the negative electrode sheet, and the concave portions have a corresponding positional relationship and the same projection shape with the convex portions. The shapes of the convex portions and the concave portions and their numbers per unit area are not limited, and the "several" means that the number of the convex portions or the concave portions is greater than or equal to 2.

[0029] In the present invention, the height of the protrusion is 3μm-40μm, for example, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 25μm, 30μm, 35μm or 40μm; the diameter of the orthographic projection of the protrusion on the surface of the negative electrode sheet is 0.1mm-16mm, for example, 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 3mm, 5mm, 7mm, 9mm, 10mm, 12mm, 14mm or 16mm.

[0030] In the present invention, the height of the convex portion refers to the maximum vertical distance from any point on the convex portion to the first surface of the negative electrode sheet. The diameter of the positive projection of the convex portion on the surface of the negative electrode sheet refers to: when the positive projection of the convex portion on the surface of the negative electrode sheet is a regular circle, the diameter of the convex portion is the diameter of the circle; when the positive projection of the convex portion on the surface of the negative electrode sheet is an irregular circle, the diameter of the convex portion is the equivalent diameter of a regular circle with the same area as the irregular circle.

[0031] In the present invention, the depth of the recess is 3μm-40μm, for example, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 25μm, 30μm, 35μm or 40μm; the diameter of the recess is 0.1mm-16mm, for example, 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 3mm, 5mm, 7mm, 9mm, 10mm, 12mm, 14mm or 16mm.

[0032] In the present invention, the diameter of the recess refers to: when the orthographic projection of the recess on the surface of the negative electrode sheet is a regular circle, the diameter of the recess is the diameter of the circle; when the orthographic projection of the recess on the surface of the negative electrode sheet is an irregular circle, the diameter of the recess is the equivalent diameter of a regular circle with the same area as the irregular circle. The depth of the recess refers to the maximum vertical distance from any point in the recess to the second surface of the negative electrode sheet.

[0033] In the present invention, the diameter of the concave portion and the diameter of the orthographic projection of the convex portion on the surface of the negative electrode sheet can be obtained by combining a 3D microscope with image analysis software, selecting 10 convex portions and concave portions on the 3D microscope image, measuring them separately and calculating their respective average values; the depth of the concave portion and the height of the convex portion can be measured using a micrometer, selecting 10 concave portions and convex portions on the negative electrode sheet, measuring them separately and calculating their respective average values. The above test results can also be obtained by other conventional testing methods in the field.

[0034] In the present invention, the contents of DFEA and D2 can be obtained by conventional testing methods in the art, such as by gas chromatography or gas chromatography-mass spectrometry.

[0035] In the present invention, the silicon-based material includes a silicon-carbon material, and the mass content of silicon in the negative electrode active material layer is C Si , C SiIt is 3%-40%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38% or 40%.

[0036] In one embodiment, C Si It is 5%-20%.

[0037] In the present invention, when C Si When the content of silicon in the negative electrode active material layer is less than 3%, the contribution to energy density is low, resulting in insignificant improvement in the energy density of the battery. Si When it is greater than 40%, due to the excessively high content of silicon in the negative electrode active material layer, the volume expansion of the battery is aggravated during the charge and discharge process, resulting in the instability of the SEI film under high temperature conditions. At the same time, the side reactions of the electrolyte are aggravated and decomposed, resulting in an increased risk of thermal runaway of the battery, and the safety performance and cycle life at high temperatures are deteriorated.

[0038] In the present invention, the mass content of silicon in the negative electrode active material layer can be measured by conventional testing methods in the art, for example, by an ICP spectrometer. The testing method is as follows: scrape 0.1 g of the negative electrode active material layer as a sample, add 10 mL of hydrochloric acid, and digest on a 350°C hot plate for 10 min. After cooling, the volume is fixed to 100 mL, and then diluted 10 times, and a portion of the solution is analyzed using an ICP spectrometer.

[0039] In the present invention, the median particle size Dv50 of the silicon-based material is 5μm-15μm, for example, 5μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, or 15μm.

[0040] In the present invention, the median particle size Dv50 of the silicon-carbon material is 5μm-15μm, for example, 5μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, or 15μm.

[0041] In the present invention, the particle size distribution of the silicon-carbon material is regulated within a certain range, which can inhibit the volume expansion and the occurrence of side reactions in the electrolyte to a certain extent, thereby optimizing the high-temperature cycle life and safety performance of the battery; when Dv50>15μm, the particle size of the silicon-based material is too large, resulting in increased volume expansion during the charge and discharge process, and when Dv50<5μm, the particle size of the silicon-based material is too small, the specific surface area of ​​the silicon-carbon material increases, and the contact area with the electrolyte increases, resulting in increased side reactions and poor high-temperature cycle performance.

[0042] In the present invention, the median particle size Dv50 of the silicon-carbon material can be obtained by conventional testing methods in the art, such as using a laser particle size analyzer and measuring by laser diffraction: the silicon-carbon material is peeled off from the current collector with NMP and dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02wt%-0.03wt%) to form a mixture, the mixture is ultrasonicated for 2 minutes, and then placed in a Malvern particle size tester for testing.

[0043] In the present invention, the compaction density of the negative electrode active material layer is 1.5 g / cm 3 -1.9g / cm 3 , for example 1.5 g / cm 3 , 1.52g / cm 3 , 1.54g / cm 3 , 1.56g / cm 3 , 1.58g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 , 1.82g / cm 3 , 1.84g / cm 3 , 1.86g / cm 3 、1.88g / cm 3 or 1.9 g / cm 3 .

[0044] In the present invention, when the compaction density of the negative electrode active material layer is greater than 1.9 g / cm 3 When the compaction density is too large, it is difficult for the electrolyte to achieve good infiltration of the negative electrode sheet, the internal resistance increases, the specific capacity of the silicon-carbon material is not fully utilized, and the high-temperature cycle capacity of the battery decays faster; when the compaction density of the negative electrode active material layer is less than 1.5g / cm 3At this time, the compaction density is too low, resulting in a decrease in the energy density of the negative electrode and an increase in the porosity, which is not conducive to electronic conductivity and an increase in discharge polarization, which in turn causes the battery to decay rapidly during high-temperature cycling and a decrease in high-temperature cycling performance.

[0045] In the present invention, the compaction density of the negative electrode active material layer can be obtained using conventional testing methods in the art, for example: take a number of negative electrode sheets per unit area (the area is denoted as S), weigh the mass of the negative electrode sheets per unit area (denoted as m1) using an analytical balance, then measure the thickness of the negative electrode sheets (denoted as d1) and the thickness of the current collector (denoted as d0) using a micrometer or a 3D microscope, then scrape off the negative electrode active material layer with an acetone solution, weigh the mass of the negative electrode current collector (denoted as m0), and calculate the compaction density of the negative electrode active material layer using the following formula: The compaction density of the negative electrode active material layer = [S / (m1−m0)] / (d1−d0).

[0046] In the present invention, the electrolyte further comprises a fluorinated benzene compound, wherein the fluorinated benzene compound is obtained by replacing the hydrogen atoms on the benzene ring with fluorine atoms, and the chemical formula is C6H 6-n F n , n is an integer of 1-6, for example, 1, 2, 3, 4, 5 or 6.

[0047] In the present invention, the fluorobenzene compound includes at least one of fluorobenzene, o-difluorobenzene (1,2-difluorobenzene), m-difluorobenzene (1,3-difluorobenzene), p-difluorobenzene (1,4-difluorobenzene), 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, 1,2,3,5-tetrafluorobenzene, 1,2,4,5-tetrafluorobenzene, pentafluorobenzene and perfluorobenzene.

[0048] In one embodiment, the fluorobenzene includes at least one of m-difluorobenzene, o-difluorobenzene, p-difluorobenzene and fluorobenzene.

[0049] In the present invention, based on the total weight of the electrolyte, the content of the fluorobenzene is F3, F3 is 2-20, and the unit is %, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18% or 20%.

[0050] In one embodiment, F3 is 5-13, and the unit is %.

[0051] In the present invention, F1, F2 and F3 satisfy 0.16≤(F1+F2) / F3≤15, for example, 0.16, 0.18, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 4, 5, 6, 8, 10, 12, 14 or 15.

[0052] In one embodiment, 0.68≤(F1+F2) / F3≤3.54.

[0053] In the present invention, the calculation of (F1+F2) / F3 only takes the numerical part for operation. For example, when F1=4%, F2=1.8%, and F3=6%, (F1+F2) / F3=(4+1.8) / 6=0.97.

[0054] In the present invention, the addition of DFEA and D2 to the electrolyte increases the viscosity of the electrolyte, thereby affecting the wettability of the electrolyte to the electrode material. The introduction of fluorobenzene compounds can reduce the surface energy between the electrolyte and the positive electrode active material layer and the negative electrode active material layer, thereby improving the spreading ability of the electrolyte on the electrode material and improving the wettability. At the same time, thanks to the high chemical stability of fluorobenzene compounds, the oxidation stability and thermal stability of the electrolyte are also improved, reducing the decomposition of the electrolyte under high temperature conditions, thereby improving the high temperature cycle life and safety performance of the battery while improving the wettability of the electrolyte. However, fluorobenzene compounds have high acidity. When the content of fluorobenzene compounds is too high, side reactions will also occur during the high temperature cycle process, affecting the safety and stability of the battery. By adjusting (F1+F2) / F3 within a certain range, the addition amounts of DFEA, D2 and fluorobenzene compounds in the electrolyte can be matched. The three complement each other, which can improve the wettability of the electrolyte, reduce the side reactions occurring in the negative electrode, and improve the high temperature safety performance of the battery.

[0055] In the present invention, the content of the fluorobenzene compound can be obtained by conventional testing methods in the art, such as by gas chromatography or gas chromatography-mass spectrometry.

[0056] In the present invention, the electrolyte further includes vinyl sulfate (DTD). Based on the total weight of the electrolyte, the content of vinyl sulfate is F4, 0.1≤F4≤1, and the unit is %, for example, 0.1%, 0.01%, 0.05%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.

[0057] In the present invention, the electrolyte also includes lithium difluorophosphate. Based on the total weight of the electrolyte, the content of the lithium difluorophosphate is F5, 0.1≤F5≤1.5, and the unit is %, for example, 0.1%, 0.05%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 1%, 1.2%, 1.3%, 1.4% or 1.5%.

[0058] In one embodiment, 0.1≤F5≤0.6, and the unit is %.

[0059] In the present invention, since the impedance increases when the addition amount of DFEA and D2 is large, the addition of DTD and / or lithium difluorophosphate can reduce the battery impedance, reduce heat accumulation, and further improve the high temperature safety performance. This is because DTD can weaken the interaction between lithium ions and solvent molecules in the electrolyte, making lithium ions easier to desolvate, improving the contact between the electrolyte and the electrode interface, enhancing the electron transfer performance, reducing polarization, and reducing the impedance of the SEI film, but when F4>1%, it will cause the acidity of the electrolyte to rise, affecting the quality of the electrolyte, so the content of DTD in the electrolyte needs to be maintained within a reasonable range; while lithium difluorophosphate can form a low-impedance solid electrolyte interface (SEI) film rich in LiF and PO compounds on the surface of the negative electrode sheet, and can also form a stable interface film (CEI) on the surface of the positive electrode sheet, effectively inhibiting the oxidative decomposition of the electrolyte and protecting the integrity of the electrode structure, but due to the poor solubility of lithium difluorophosphate, when F5>1.5%, lithium difluorophosphate will precipitate at low temperatures, causing unevenness inside the battery.

[0060] In the present invention, the electrolyte further includes lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). Based on the total weight of the electrolyte, the content of lithium bis(trifluoromethylsulfonyl)imide is F6, 1≤F6≤12, and the unit is %, for example, 1%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11% or 12%.

[0061] In one embodiment, 2≤F6≤9, the unit is %.

[0062] In the present invention, LiTFSI has better thermal stability, and its decomposition temperature is higher than 200°C. In addition, during the charge and discharge process of the battery, LiTFSI helps to form a stable solid electrolyte interface (SEI) film on the electrode surface to prevent further decomposition of the electrolyte, thereby improving the cycle stability of the battery at high temperatures. Adding LiTFSI to the electrolyte to replace a portion of lithium hexafluorophosphate can improve the stability of the electrolyte and the high-temperature performance of the battery. However, when F6>12%, the viscosity of the electrolyte will increase and the aluminum foil will corrode.

[0063] In the present invention, the electrolyte further comprises tripropargyl phosphate (TPP, structural formula: ), based on the total weight of the electrolyte, the content of the tripropargyl phosphate is F7, 0.1≤F7≤0.5, and the unit is %, for example, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%.

[0064] In the present invention, by introducing TPP into the electrolyte, the dissolution of cobalt in the positive electrode and its deposition on the negative electrode can be suppressed, and the aggravation of the side reaction of the negative electrode can be avoided. This is because TPP contains three carbon-carbon triple bond unsaturated functional groups, which can form a dense and protective CEI film on the surface of the positive electrode sheet. This CEI film can effectively inhibit the dissolution of cobalt in the positive electrode and its migration to the negative electrode, avoid the aggravation of the side reaction on the negative electrode, and improve the safety and stability of the battery; however, TPP has a large molecular weight, a high melting point, and a low dielectric constant, which will increase the freezing point of the electrolyte and increase the inter-ionic force, but when F7>0.5%, it will inhibit the dissociation of lithium salts.

[0065] In the present invention, the contents of TPP and LiTFSI can be obtained by conventional testing methods in the art, such as by gas chromatography or gas chromatography-mass spectrometry.

[0066] In the present invention, the electrolyte further comprises an organic solvent, a lithium salt and other additives.

[0067] In the present invention, the organic solvent includes at least one of fluorine-substituted or unsubstituted carbonates and fluorine-substituted or unsubstituted carboxylates, the carbonates include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl butyrate (EB), dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC). The carboxylates include at least one of ethyl acetate (EA), propyl acetate, n-butyl acetate, isobutyl acetate, methyl propionate (MP), propyl propionate (PP), ethyl propionate (EP), methyl butyrate and ethyl butyrate.

[0068] In the present invention, the other additives include at least one of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (PS), tetravinylsilane (TVS), tris(trimethylsilyl)borate (TMSB), hexamethyldisilazane (HMDS), triphenyl phosphite (TPPi), benzonitrile, p-toluenenitrile, 3,5-difluorobenzonitrile, adiponitrile (AND), succinonitrile (SN), glutaronitrile, suberonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile (HTCN), 1,2,6-hexanetrinitrile and 1,2,3-tris(2-cyanoethoxy)propane.

[0069] In the present invention, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 4,5-dicyano-2-trifluoromethylimidazolium (LiDTI) and lithium difluorobis(oxalatophosphate).

[0070] In the present invention, the negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder. Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material is 80%-98.5%, for example, 80%, 80.5%, 81%, 81.5%, 82%, 82.5%, 83%, 83.5%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 96.5%, 97%, 97.5%, 98% or 98.5%. The content of the negative electrode conductive agent is 0.1%-10%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. The content of the negative electrode binder is 0.1%-10%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0071] In one embodiment, based on the total weight of the negative electrode active material layer, the content of the negative electrode active material is 89%-99.5%, the content of the negative electrode conductive agent is 0.1%-5%, and the content of the negative electrode binder is 0.1%-5%.

[0072] In the present invention, the negative electrode active material includes the silicon-based material.

[0073] In the present invention, the lithium ion battery further includes a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder.

[0074] In the present invention, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material is 80% - 99.8%, for example, 80%, 80.5%, 81%, 81.5%, 82%, 82.5%, 83%, 83.5%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.4% or 99.8%. The content of the positive electrode conductive agent is 0.1% - 10%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. The content of the positive electrode binder is 0.1% - 10%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0075] In one embodiment, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material is 90% - 99.6%, the content of the positive electrode conductive agent is 0.2% - 5%, and the content of the positive electrode binder is 0.2% - 5%.

[0076] In the present invention, the positive electrode active material includes lithium cobaltate or a ternary material of chemical formula LiNi x Co y Mn z M a O2, where 0.3 ≤ x ≤ 0.99, 0 < y ≤ 0.35, 0 < z ≤ 0.35, 0 ≤ b ≤ 0.05, and M is selected from at least one of Al, Zr, B, Y, Sr, W, Ti, and Nb.

[0077] In one embodiment, the positive electrode active material includes lithium cobaltate.

[0078] In yet another embodiment, the positive electrode active material includes lithium cobaltate and a chemical formula of LiNi x Co y Mnz M a O2, the mass content of the ternary material in the lithium cobalt oxide is 0-15%.

[0079] In the present invention, the ternary material is introduced into the positive electrode active material, which can improve the stability while maintaining high specific energy. The introduction of Ni can increase the separation of Co 3d and O 2p energy bands, reduce the instability of O under high voltage, and further improve the stability of the positive electrode active material. However, due to the addition of Ni 3+ The thermal stability is poor, and excessive introduction of Ni will lead to poor high temperature performance and structural stability.

[0080] In the present invention, the positive electrode conductive agent and the negative electrode conductive agent are each independently selected from at least one of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers and graphene.

[0081] In the present invention, the positive electrode binder and the negative electrode binder are each independently selected from at least one of polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyethylene oxide, sodium carboxymethyl cellulose and polyvinylidene fluoride.

[0082] In the present invention, the lithium-ion battery further comprises a separator, and the separator comprises one of polyethylene (PE), polypropylene (PP), and a composite separator of PP and PE.

[0083] In the present invention, the positive electrode current collector and the negative electrode current collector are both conventionally selected by those skilled in the art.

[0084] The present invention also provides an electronic device including the lithium ion secondary battery. The present invention is not particularly limited to the electronic device, which can be used for any electronic device known in the prior art. The electronic device includes, for example, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery or a lithium ion capacitor, etc.

[0085] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0086] The present invention will be described in detail below through embodiments, and the embodiments described in the present invention are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0087] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0088] The following examples are used to illustrate the lithium ion battery of the present invention.

[0089] Embodiment 1: Preparation of positive electrode sheet: The positive electrode active material, conductive carbon black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone at a mass ratio of 96.1:2.4:1.5, and fully stirred to form a uniform positive electrode active material slurry. The positive electrode active material slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, rolling and cutting. Among them, the positive electrode active material is LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.33 Co 0.33 Mn 0.33 The mass fraction of O2 in LiCoO2 is 8%.

[0090] Preparation of negative electrode sheet: Weigh artificial graphite and silicon carbon (mass content of silicon element in negative electrode active material layer C Si = 12%), conductive carbon black, styrene-butadiene rubber, and sodium carboxymethyl cellulose are dispersed in an appropriate amount of deionized water in a mass ratio of 85.5:11.7:0.5:1.0:1.3, and fully stirred to form a uniform negative electrode active material slurry. The negative electrode active material slurry is coated on the negative electrode current collector copper foil, and then dried. The negative electrode is embossed by rolling with an embossing roller, and cut to obtain a negative electrode sheet. Among them, the diameter of the positive projection of the convex part on the surface of the negative electrode sheet is 2mm, the height is 30μm, the diameter of the concave part is 2mm, and the depth is 30μm. At this time, the ratio of the sum of the positive projection areas of the convex part on the first surface to the area of ​​the negative electrode sheet is 0.135.

[0091] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / EP were mixed in a mass ratio of 1:1:1, and then 13% of fully dried lithium hexafluorophosphate (LiPF6) and 6.8% of fully dried LiTFSI were added thereto based on the total weight of the electrolyte. After dissolution, 9.7% DFEA, 4% D2, 7% p-difluorobenzene, 0.7% DTD, 0.2% lithium difluorophosphate, and 0.2% TPP were added based on the total weight of the electrolyte. The mixture was stirred evenly. After passing the moisture and free acid tests, the required non-aqueous electrolyte was obtained.

[0092] Assembly of lithium-ion batteries: The prepared positive electrode sheet, negative electrode sheet and separator (porous polymer film) are placed in order, with the separator between the positive and negative electrode sheets. The electrodes are then welded and wound to obtain a core. The core is then placed in an aluminum-plastic film packaging bag. The process of liquid injection, formation, secondary sealing and sorting is then carried out to prepare a lithium-ion battery. Finally, the electrical performance of the battery is tested.

[0093] Embodiment 2: Preparation of positive electrode sheet: The positive electrode active material, conductive carbon black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone at a mass ratio of 96.1:2.4:1.5, and fully stirred to form a uniform positive electrode active material slurry. The positive electrode active material slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, rolling and cutting. Among them, the positive electrode active material is LiCoO2 and LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.5 Co 0.2 Mn 0.3 The mass fraction of O2 in LiCoO2 is 8%.

[0094] Preparation of negative electrode sheet: Weigh artificial graphite and silicon carbon (mass content of silicon element in negative electrode active material layer C Si = 12%), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are dispersed in an appropriate amount of deionized water in a mass ratio of 85.5:11.7:0.5:1.0:1.3, and fully stirred to form a uniform negative electrode active material slurry. The negative electrode active material slurry is coated on the negative electrode current collector copper foil, and then dried. The negative electrode is embossed by rolling with an embossing roller, and cut to obtain a negative electrode sheet. Among them, the diameter of the positive projection of the convex part on the surface of the negative electrode sheet is 1mm, the height is 3μm, the diameter of the concave part is 1mm, and the depth is 3μm. At this time, the ratio of the sum of the positive projection areas of the convex part on the first surface to the area of ​​the negative electrode sheet is 0.21.

[0095] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / EP were mixed in a mass ratio of 1:1:1, and then 13% of fully dried lithium hexafluorophosphate (LiPF6) and 2% of fully dried LiTFSI were added thereto based on the total weight of the electrolyte. After dissolution, 11.5% DFEA, 6.2% D2, 5% o-difluorobenzene, 0.65% DTD, 0.25% lithium difluorophosphate, and 0.27% TPP were added based on the total weight of the electrolyte. The mixture was stirred evenly. After passing the moisture and free acid tests, the required non-aqueous electrolyte was obtained.

[0096] Assembly of lithium-ion batteries: The prepared positive electrode sheet, negative electrode sheet and separator (porous polymer film) are placed in order, with the separator between the positive and negative electrode sheets. The electrodes are then welded and wound to obtain a core. The core is then placed in an aluminum-plastic film packaging bag. The process of liquid injection, formation, secondary sealing and sorting is then carried out to prepare a lithium-ion battery. Finally, the electrical performance of the battery is tested.

[0097] Embodiment 3: Preparation of positive electrode sheet: The positive electrode active material, conductive carbon black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone at a mass ratio of 96.1:2.4:1.5, and fully stirred to form a uniform positive electrode active material slurry. The positive electrode active material slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, rolling and cutting. Among them, the positive electrode active material is LiCoO2 and LiNi 0.5 Co 0.2 Mn 0.27 Al 0.03 O2, LiNi 0.5 Co 0.2 Mn 0.27 Al 0.03 The mass fraction of O2 in LiCoO2 is 8%.

[0098] Preparation of negative electrode sheet: Weigh artificial graphite and silicon carbon (mass content of silicon element in negative electrode active material layer C Si = 12%), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are dispersed in an appropriate amount of deionized water in a mass ratio of 85.5:11.7:0.5:1.0:1.3, and fully stirred to form a uniform negative electrode active material slurry. The negative electrode active material slurry is coated on the negative electrode current collector copper foil, and then dried. The negative electrode is embossed by rolling with an embossing roller, and cut to obtain a negative electrode sheet. Among them, the diameter of the positive projection of the convex part on the surface of the negative electrode sheet is 16mm, the height is 25μm, the diameter of the concave part is 16mm, and the depth is 25μm. At this time, the ratio of the sum of the positive projection areas of the convex part on the first surface to the area of ​​the negative electrode sheet is 0.4.

[0099] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / EP were mixed in a mass ratio of 1:1:1, and then 13% of fully dried lithium hexafluorophosphate (LiPF6) and 9% of fully dried LiTFSI were added thereto based on the total weight of the electrolyte. After dissolution, 2% DFEA, 7% D2, 13% fluorobenzene, 0.72% DTD, 0.32% lithium difluorophosphate, and 0.25% TPP were added based on the total weight of the electrolyte. The mixture was stirred evenly. After passing the moisture and free acid tests, the required non-aqueous electrolyte was obtained.

[0100] Assembly of lithium-ion batteries: The prepared positive electrode sheet, negative electrode sheet and separator (porous polymer film) are placed in order, with the separator between the positive and negative electrode sheets. The electrodes are then welded and wound to obtain a core. The core is then placed in an aluminum-plastic film packaging bag. The process of liquid injection, formation, secondary sealing and sorting is then carried out to prepare a lithium-ion battery. Finally, the electrical performance of the battery is tested.

[0101] Embodiment 4: Preparation of positive electrode sheet: The positive electrode active material, conductive carbon black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 96.1:2.4:1.5, and fully stirred to form a uniform positive electrode active material slurry. The positive electrode active material slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, rolling and cutting; wherein the positive electrode active material is LiCoO2.

[0102] Preparation of negative electrode sheet: Weigh artificial graphite and silicon carbon (mass content of silicon element in negative electrode active material layer C Si = 12%), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are dispersed in an appropriate amount of deionized water in a mass ratio of 85.5:11.7:0.5:1.0:1.3, and fully stirred to form a uniform negative electrode active material slurry. The negative electrode active material slurry is coated on the negative electrode current collector copper foil, and then dried. The negative electrode is embossed by rolling with an embossing roller, and cut to obtain a negative electrode sheet. Among them, the diameter of the positive projection of the convex part on the surface of the negative electrode sheet is 10mm, the height is 40μm, the diameter of the concave part is 10mm, and the depth is 40μm. At this time, the ratio of the sum of the positive projection areas of the convex part on the first surface to the area of ​​the negative electrode sheet is 0.1.

[0103] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / EP were mixed in a mass ratio of 1:1:1, and then 13% of fully dried lithium hexafluorophosphate (LiPF6) and 5.2% of fully dried LiTFSI were added thereto based on the total weight of the electrolyte. After dissolution, 13% DFEA, 2% D2, 7.8% m-difluorobenzene, 0.59% DTD, 0.34% lithium difluorophosphate, and 0.18% TPP were added based on the total weight of the electrolyte. The mixture was stirred evenly. After passing the moisture and free acid tests, the required non-aqueous electrolyte was obtained.

[0104] Assembly of lithium-ion batteries: The prepared positive electrode sheet, negative electrode sheet and separator (porous polymer film) are placed in order, with the separator between the positive and negative electrode sheets. The electrodes are then welded and wound to obtain a core. The core is then placed in an aluminum-plastic film packaging bag. The process of liquid injection, formation, secondary sealing and sorting is then carried out to prepare a lithium-ion battery. Finally, the electrical performance of the battery is tested.

[0105] Embodiment 5 group: This group of embodiments is used to verify the value of "(F1+F2) / S", that is, the impact of regulating the relationship between F1, F2 and S.

[0106] Based on Example 1, the difference is that the sizes of S, F1 and F2 are changed by adjusting the diameter of the protrusions, the amount of DFEA and D2 added to the electrolyte, as follows: Example 5a, during the preparation of the negative electrode sheet, the diameter of the orthographic projection of the convex portion on the surface of the negative electrode sheet is 0.1 mm, and the height is 30 μm. The diameter of the concave portion is 0.1 mm, and the depth is 30 μm. At this time, the ratio of the sum of the orthographic projection areas of the convex portion on the first surface to the area of ​​the negative electrode sheet is 0.03; during the preparation of the electrolyte, 19.8% DFEA and 9.7% D2 are added based on the total weight of the electrolyte.

[0107] Example 5b, during the preparation of the negative electrode sheet, the diameter of the orthographic projection of the convex portion on the surface of the negative electrode sheet is 12.5 mm, and the height is 30 μm. The diameter of the concave portion is 12.5 mm, and the depth is 30 μm. At this time, the ratio of the sum of the orthographic projection areas of the convex portion on the first surface to the area of ​​the negative electrode sheet is 0.6. During the preparation of the electrolyte, 1.05% DFEA and 0.1% D2 are added based on the total weight of the electrolyte.

[0108] Example 5c, during the preparation of the negative electrode sheet, the diameter of the orthographic projection of the convex portion on the surface of the negative electrode sheet was 0.8 mm, and the height was 30 μm. The diameter of the concave portion was 0.8 mm, and the depth was 30 μm. At this time, the ratio of the sum of the orthographic projection areas of the convex portion on the first surface to the area of ​​the negative electrode sheet was 0.28. During the preparation of the electrolyte, 3.5% DFEA and 2.2% D2 were added based on the total weight of the electrolyte.

[0109] Example 5d, during the preparation of the negative electrode sheet, the diameter of the orthographic projection of the convex portion on the surface of the negative electrode sheet is 16 mm, and the height is 25 μm. The diameter of the concave portion is 16 mm, and the depth is 25 μm. At this time, the ratio of the sum of the orthographic projection areas of the convex portion on the first surface to the area of ​​the negative electrode sheet is 0.3; during the preparation of the electrolyte, 3% DFEA and 2% D2 are added based on the total weight of the electrolyte.

[0110] Example 5e, during the preparation of the negative electrode sheet, the diameter of the orthographic projection of the convex portion on the surface of the negative electrode sheet is 10 mm, and the height is 40 μm. The diameter of the concave portion is 10 mm, and the depth is 40 μm. At this time, the ratio of the sum of the orthographic projection areas of the convex portion on the first surface to the area of ​​the negative electrode sheet is 0.1. During the preparation of the electrolyte, 13% DFEA and 7% D2 are added based on the total weight of the electrolyte.

[0111] The calculation results of “(F1+F2) / S” are shown in Table 1.

[0112] Embodiment 6 group: This group of embodiments is used to verify the formula "(F1+F2) / F3" and regulate the impact of the relationship between F1, F2 and F3.

[0113] Based on Example 1, the difference is that the size of F1, F2 and F3 is changed by adjusting the amount of DFEA, D2 and fluorobenzene compounds added to the electrolyte, as follows: In Example 6a, during the preparation of the electrolyte, 19.6% DFEA, 9.7% D2, and 2% p-difluorobenzene were added based on the total weight of the electrolyte, and the rest were consistent with Example 1.

[0114] In Example 6b, during the preparation of the electrolyte, 2% DFEA, 0.97% D2, and 19.8% p-difluorobenzene were added based on the total weight of the electrolyte, and the rest was consistent with Example 1.

[0115] In Example 6c, during the preparation of the electrolyte, 3.5% DFEA, 2.1% D2, and 8.2% p-difluorobenzene were added based on the total weight of the electrolyte, and the rest were consistent with Example 1.

[0116] In Example 6d, during the preparation of the electrolyte, 3.5% DFEA, 2.1% D2, and 0% p-difluorobenzene were added based on the total weight of the electrolyte, and the rest were consistent with Example 1.

[0117] In Example 6e, during the preparation of the electrolyte, 9.7% DFEA, 4% D2, and 7% pentafluorobenzene were added based on the total weight of the electrolyte, and the rest were consistent with Example 1.

[0118] In Example 6f, during the preparation of the electrolyte, 9.7% DFEA, 4% D2, and 7% perfluorobenzene were added based on the total weight of the electrolyte, and the rest were consistent with Example 1.

[0119] The calculation results of “(F1+F2) / F3” are shown in Table 1.

[0120] Embodiment 7 group: This group of examples is used to verify the effect of the amount of DTD added to the electrolyte.

[0121] Based on Example 1, the difference is that the addition amount of DTD in the electrolyte is adjusted, as follows: In Example 7a, during the preparation of the electrolyte, the content of DTD was 0% based on the total weight of the electrolyte, and the rest was consistent with Example 1.

[0122] In Example 7b, during the preparation of the electrolyte, the content of DTD was 1% based on the total weight of the electrolyte, and the rest was consistent with Example 1.

[0123] In Example 7c, during the preparation of the electrolyte, DTD was replaced with PST. Based on the total weight of the electrolyte, the content of PST was 0.7%, and the rest was consistent with Example 1.

[0124] Embodiment 8 group: This group of examples is used to verify the effect of the amount of lithium difluorophosphate added to the electrolyte.

[0125] Based on Example 1, the difference is that the addition amount of lithium difluorophosphate in the electrolyte is adjusted, as follows: In Example 8a, during the preparation of the electrolyte, the content of lithium difluorophosphate was 0% based on the total weight of the electrolyte, and the rest was consistent with Example 1.

[0126] In Example 8b, during the preparation of the electrolyte, the content of lithium difluorophosphate was 1.5% based on the total weight of the electrolyte, and the rest was consistent with Example 1.

[0127] In Example 8c, during the preparation of the electrolyte, lithium difluorophosphate was replaced with lithium difluorooxalate (LiODFB). Based on the total weight of the electrolyte, the content of LiODFB was 0.2%, and the rest was consistent with Example 1.

[0128] Embodiment 9 group: This group of examples is used to verify the effect of the amount of LiTFSI added to the electrolyte.

[0129] Based on Example 1, the difference is that it is achieved by adjusting the amount of LiTFSI added in the electrolyte, as follows: In Example 9a, during the preparation of the electrolyte, the content of LiTFSI based on the total weight of the electrolyte was 1.1%, and the rest was consistent with Example 1.

[0130] In Example 9b, during the preparation of the electrolyte, the content of LiTFSI was 11.8% based on the total weight of the electrolyte, and the rest was consistent with Example 1.

[0131] In Example 9c, during the preparation of the electrolyte, LiTFSI was not added, and only lithium hexafluorophosphate was added. Based on the total weight of the electrolyte, the total content of lithium hexafluorophosphate was 19.8%, and the rest was consistent with Example 1.

[0132] Example 10 Group: This group of examples is used to verify the effect of the amount of TPP added to the electrolyte.

[0133] Based on Example 1, the difference is that the addition amount of TPP in the electrolyte is adjusted, as follows: In Example 10a, during the preparation of the electrolyte, the content of TPP was 0% based on the total weight of the electrolyte, and the rest was consistent with Example 1.

[0134] In Example 10b, during the preparation of the electrolyte, the content of TPP was 0.49% based on the total weight of the electrolyte, and the rest was consistent with Example 1.

[0135] Embodiment 11 group: This group of examples is used to verify the mass content of silicon element C in the negative electrode active material layer Si The impact produced.

[0136] Based on Example 1, the difference is that the C is regulated by changing the mass content of the silicon-based material in the negative electrode active material. Si The implementation is as follows: In Example 11a, during the preparation of the negative electrode sheet, the mass content of silicon in the negative electrode active material layer was adjusted to 3.2%, and the rest was consistent with Example 1.

[0137] In Example 11b, during the preparation of the negative electrode sheet, the mass content of silicon in the negative electrode active material layer was adjusted to 5%, and the rest was consistent with Example 1.

[0138] In Example 11c, during the preparation of the negative electrode sheet, the mass content of silicon in the negative electrode active material layer was adjusted to 20.4%, and the rest was consistent with Example 1.

[0139] In Example 11d, during the preparation of the negative electrode sheet, the mass content of silicon in the negative electrode active material layer was adjusted to 39.7%, and the rest was consistent with Example 1.

[0140] Comparative Example 1: Based on Example 1, the difference is that in the process of preparing the electrolyte, DFEA is not added, that is, F1=0, and the rest is consistent with Example 1.

[0141] Comparative Example 2: Based on Example 1, the difference is that D2 is not added during the preparation of the electrolyte, that is, F2=0, and the rest is consistent with Example 1.

[0142] Comparative Example 3: Based on Example 1, the difference is that in the process of preparing the electrolyte, DFEA and D2 are not added, that is, F1=0, F2=0, and the rest is consistent with Example 1.

[0143] Comparative Example 4: This group is used to verify the effect of regulating "(F1+F2) / S", which is achieved by adjusting the ratio S of the sum of the positive projection areas of DFEA, D2 and the convex part on the first surface to the area of ​​the negative electrode sheet, as follows: Comparative Example 4a: During the preparation of the negative electrode sheet, the ratio of the sum of the orthographic projection areas of the protrusions on the first surface to the area of ​​the negative electrode sheet was 0.5; during the preparation of the electrolyte, 1.5% DFEA and 0.85% D2 were added based on the total weight of the electrolyte.

[0144] Comparative Example 4b: During the preparation of the negative electrode sheet, the ratio of the sum of the orthographic projection areas of the protrusions on the first surface to the area of ​​the negative electrode sheet was 0.027; during the preparation of the electrolyte, 30% DFEA and 10.5% D2 were added based on the total weight of the electrolyte.

[0145] In all embodiments, an orthographic projection area of ​​the convex portion on the first surface accounts for 80%-120% of an orthographic projection area of ​​the concave portion on the second surface.

[0146] Test Example 1: Determination of median particle size of silicon carbon materials: Use a laser particle size analyzer and laser diffraction to measure: Use NMP to peel off the negative electrode active material from the current collector and disperse it in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, content of 0.02wt%-0.03wt%) to form a mixture. Ultrasonicate the mixture for 2 minutes and then put it into the Malvern particle size tester for testing.

[0147] In the above embodiments, the median particle size of the silicon-carbon material is in the range of 5-15 μm.

[0148] Test Example 2: Determination of compaction density of negative electrode active material layer: Take a number of negative electrode sheets per unit area (area is denoted as S), weigh the mass of the negative electrode sheets per unit area (denoted as m1) using an analytical balance, measure the thickness of the negative electrode sheets (denoted as d1) and the thickness of the current collector (denoted as d0) using a micrometer or a 3D microscope, scrape off the negative electrode active material layer with an acetone solution, weigh the mass of the negative electrode current collector (denoted as m0), and calculate the compaction density of the negative electrode active material layer using the following formula: The compaction density of the negative electrode active material layer = [S / (m1−m0)] / (d1−d0).

[0149] In the above embodiments, the compaction density of the negative electrode active material layer is 1.5-1.9 g / cm 3 within the range.

[0150] Test Example 3: Battery performance test: (1) Cycle performance test: Place the lithium-ion battery in a 45°C environment and let it stand for 2 hours. When the battery temperature is 45±2°C, charge it to the upper limit voltage (4.53V) at a constant current of 1C, let it stand for 5 minutes and measure the thickness as H0. Then discharge it to 3.0V at a constant current of 0.5C and let it stand for 5 minutes. This is a charge and discharge cycle, and the charge and discharge cycle is 500 times. The highest discharge capacity of the first three cycles is recorded as the initial capacity Q0, the discharge capacity of the 500th cycle is Q1, and the thickness after the battery is fully charged is H1. Calculate the battery capacity retention rate = Q1 / Q0×100%; thickness change rate = H1 / H0×100%; (2) EIS impedance test: discharge at 0.2C to 3.0V at 25℃±5℃; let stand for 10min; adjust SOC: charge at 0.7C constant current to 50% SOC of capacity, let stand for 10min; test the internal resistance in the half-charge state, and then perform AC impedance test, fit the test data, and output the data battery impedance R (unit: mΩ).

[0151] (3) 130℃ thermal shock test: The above lithium-ion battery is subjected to a 130℃ thermal shock test. The test process is as follows: first, the battery is charged to the upper limit voltage at a constant current and voltage of 0.7C, and the cut-off current is 0.05C. The initial state of the battery, including voltage, internal resistance, thickness, etc., is tested; then the above battery is placed in a convection or circulating hot air oven, heated at an initial temperature of 25±3℃, and the heating rate is 5±2℃. The test is terminated after the temperature is raised to 130±2℃ and maintained for 60 minutes. The passing standard of the 130℃ thermal shock test is: the battery cell does not catch fire and does not explode, where 15 / 15 means: 15 times passed in 15 tests; 14 / 15 means: 14 times passed in 15 tests; and so on.

[0152] The test results of the battery performance are shown in Table 3.

[0153] Table 1: Table 2: It can be seen from Table 2 that the lithium ion battery prepared by the present invention has good high temperature cycle performance and safety compared with the comparative example.

[0154] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode sheet and an electrolyte; the negative electrode sheet comprises a first surface and a second surface which are opposite to each other in a thickness direction, the first surface comprises a plurality of convex portions, the second surface comprises a plurality of concave portions, the convex portions correspond to the concave portions, and the ratio of the sum of the orthogonal projection areas of the convex portions on the first surface to the area of ​​the negative electrode sheet is S, with a unit of 1; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a silicon-based material; The electrolyte includes ethyl 2,2-difluoroacetate and 1,1,2,2,-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and based on the total weight of the electrolyte, the content of ethyl 2,2-difluoroacetate is F1, and the content of 1,1,2,2,-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is F2; F1, F2 and S satisfy 1.9≤(F1+F2) / S≤984.

2. The lithium ion battery according to claim 1, wherein 16.67≤(F1+F2) / S≤200; and / or, S is 0.03-0.6, unit is 1; And / or, F1 is 1-20, unit is %; And / or, F2 is 0.1-10, in %.

3. The lithium ion battery according to claim 1 or 2, wherein S is 0.1-0.4, and the unit is 1; And / or, F1 is 2-13, unit is %; And / or, F2 is 2-7, in %.

4. The lithium ion battery according to claim 1, wherein: The silicon-based material includes a silicon-carbon material; And / or, the mass content of silicon in the negative electrode active material layer is C Si , C Si 3%-40%; and / or, the median particle size Dv50 of the silicon-based material is 5 μm-15 μm; And / or, the compaction density of the negative electrode active material layer is 1.5 g / cm 3 -1.9g / cm 3 .

5. The lithium ion battery according to claim 1, wherein: The electrolyte further comprises a fluorinated benzene compound; the electrolyte satisfies at least one of the following conditions: (x) the fluorinated benzene compound includes at least one of fluorobenzene, o-difluorobenzene, m-difluorobenzene, p-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, 1,2,3,5-tetrafluorobenzene, 1,2,4,5-tetrafluorobenzene, pentafluorobenzene and perfluorobenzene; (y) Based on the total weight of the electrolyte, the content of the fluorinated benzene compound is F3, F3 is 2-20, and the unit is %; (z) F1, F2 and the content of the fluorobenzene compound F3 satisfy 0.16≤(F1+F2) / F3≤15.

6. The lithium ion battery according to claim 5, wherein: The fluorinated benzene compound includes at least one of m-difluorobenzene, o-difluorobenzene, p-difluorobenzene and fluorobenzene; And / or, F3 is 5-13, unit is %; And / or, 0.68≤(F1+F2) / F3≤3.

54.

7. The lithium ion battery according to claim 1, wherein: The electrolyte further includes vinyl sulfate. Based on the total weight of the electrolyte, the content of the vinyl sulfate is F4, 0.1≤F4≤1, and the unit is %; And / or, the electrolyte further includes lithium difluorophosphate, and the content of the lithium difluorophosphate is F5, 0.1≤F5≤1.5, based on the total weight of the electrolyte, in %.

8. The lithium ion battery according to claim 1, wherein: The electrolyte further comprises lithium bis(trifluoromethylsulfonyl)imide. Based on the total weight of the electrolyte, the content of lithium bis(trifluoromethylsulfonyl)imide is F6, 1≤F6≤12, and the unit is %.

9. The lithium ion battery according to claim 1, wherein: The electrolyte further includes tripropargyl phosphate, and the content of the tripropargyl phosphate is F7, 0.1≤F7≤0.5, based on the total weight of the electrolyte, and the unit is %.

10. An electronic device, characterized in that: The electronic device comprises the lithium ion battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Pole piece and battery cell

    CN107681116A

  • Electrolyte and battery comprising same

    CN115842166A

  • High-voltage lithium battery electrolyte containing fluoro ester group and lithium battery

    CN116435604A

  • High-voltage electrolyte for lithium metal capacitor and capacitor

    CN117497334A

  • Battery

    CN117497850A

Cited By

  • Battery and electric device

    CN120165038A

  • Battery and electric apparatus

    EP4815094A1

  • Electrode sheet, electrode assembly and battery

    WO2026149505A1